Smallholder apiculture development in Bure, Ethiopia: experiences from IPMS project interventions - Dessalegn, Yigsaw; Hoekstra, Dirk; Berhe, Kahsay; Derso, T.; Mehari, Y. (International Livestock Research Institute, 2010)
Beekeeping has a long history in Bure district as in other parts of Ethiopia. On average, it is estimated that 110 tons of honey are produced annually by smallholder farmers, and approximately 5000 households (hhs) are engaged in beekeeping as a sideline income generating activity, including landless farmers. Most beekeepers use local hives and beekeeping practices. Consequently, the quantity and quality of honey produced in the district was very low. The Office of Agriculture and Rural Development (OoARD) in Bure and the Regional BoARD started addressing these problems in 2004 through a campaign style distribution of modern hives and processing equipments.